TONGKAT UNTUK PEMANDU ARAH KIBLAT BAGI PENYANDANG TUNANETRA - Miranda, Ayu; Haritsah Amrullah, Muhammad; Sulistyo, Eko; Saputra, Zanu (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Qibla direction guide stick specially designed for blind people. This stick is equipped with HC SR04 Ultrasonic Sensor to detect surrounding objects, HMC5883L Compass Sensor to determine the Qibla direction, and a control system that uses Arduino Uno as the programming brain. The development method involves the design and integration stages of these sensors, as well as the development to process sensor data to produce qibla direction information. The results show that this qibla direction guide stick can be used effectively, providing timely and accurate feedback to the user. Thus, the development of this technology has great potential to improve the independence and quality of life of blind people in their religious practices. This study makes an important contribution in the field of technology expanding the possibilities for blind people to participate fully in religious activities.